Test of Level of Likes on Fermentation Length and Physical Quality Characteristics of Robusta Coffee After Storage - Eva Rosdiana; Jayana Erliana; Fandyka Yufriza Ali; Setyoko, Ujang; Devina Cinantya Anindita (Jurnal Riset Perkebunan, 2024)
One of the stages in the wet processing of coffee that can affect its flavor is fermentation. Fermentation is the process of removing the mucilage layer that still adheres to the coffee beans, which results in a distinctive coffee aroma and reduces caffeine content, especially in robusta coffee. After the fermentation process, packaging and storage are carried out. Storage is the stage where raw coffee beans are kept to maintain their quality until the next process. This study aims to determine the effect of fermentation duration on panelists' preference levels and the impact of storage duration on the physical quality characteristics of robusta coffee. This research employs both quantitative and qualitative descriptive methods. The results show that storage duration does not affect the physical quality characteristics of robusta coffee beans. The moisture content parameter after storage was found to be 12.2%, the density parameter averaged 0.691 gr/ml, and the defect value parameter fell into grade 3. The study also shows that different fermentation durations do not significantly affect the panelists' preference levels, with an average score of 3-4,1.